The seventh sense : power, fortune, and survival in the age of networks (2016)
Endless terror. Refugee waves. An unfixable global economy. Surprising election results. New billion-dollar fortunes. Miracle medical advances. What if they were all connected? What if you could understand why? The Seventh Sense examines the historic force now shaking our world -- and explains how our leaders, our businesses, and each of us can master it. All around us now we are surrounded by events that are difficult to understand. But every day, new figures and forces emerge that seem to have mastered this tumultuous age. Sometimes these are the leaders of the most earthshaking companies of our time, accumulating billion-dollar fortunes. Or they are successful investors or our best generals. Other times, however, quick success is going to terrorists, rebels, and figures intent on chaos. The Seventh Sense is the story of what all of today's successful figures see and feel -- forces that are invisible to most of us but explain everything from explosive technological change to uneasy political ripples. The secret to power now is understanding our new age of networks -- not merely the Internet but also networks of trade and DNA and finance. Based on his years of advising generals, CEOs, and politicians, Ramo takes us into the opaque heart of our world's rapidly connected systems and teaches us what the victors of this age know -- and what the losers are not yet seeing.